(untitled) - Paseta, Senia; Senia Paseta (Oxford,New York, 2003)
This is a book about the Irish Question, or more specifically about Irish Questions. The term has become something of a catch-all, a convenient way to encompass numerous issues and developments which pertain to the political, social, and economic history of modern Ireland. It is a question which refuses to go away, but it is also a question whose inconstant meaning is rarely anatomized and still less often denied. One of the main aims of this book is to explore the complicated and shifting nature of the Irish Question, and to assess what it has meant to various political minds and agendas. The book is arranged both thematically and chronologically; each of the eight chapters takes as its focus a particular period, and each period is discussed within the context of one or more questions which informed and shaped that particular period
Keywords: Ireland; Ireland; Ireland